A comprehensive review on nutritive value, phytochemicals, and pharmacological activities of Ocimum basilicum var. thyrsiflora - Akankshya Sahu; Gayatree Nayak; Sanat Kumar Bhuyan; Ruchi Bhuyan; Dattatreya Kar; Ananya Kuanar (Shahrekord University of Medical Sciences, 2023)
The genus Ocimum has many species belonging to the Lamiaceae family that are used to treat various diseases and disorders. Ocimum basilicum has been found to contain over 200 chemical components in different plant parts. The bioactive components showed the presence of α-linalool, camphor, limonene, thymol, citral, β-linalool, estragole, etc. O. basilicum exhibits anti-inflammatory, antioxidant, antiulcer, antiviral, hypoglycemic, hypolipidemic, antimicrobial, anticancer, wound-healing activities, etc. They have also been used to treat fevers, digestive issues, stomach cramps, nausea, gastritis, migraine, diarrhea. This review aims to provide information about the chemical compounds and biological activities of O. basilicum var thyrsiflora (Thai basil). To the best of our knowledge, this is the first review outlining the innovative ethnomedicinal approach to oral health care that, through its strong phytoconstituents, has the potential to improve modern medicine.